Perancangan Interior Gereja Bethel Indonesia Representative Of Christ Kingdom (R.O.C.K) City Square di Surabaya - Monica Marcellia; Stephanus P Honggowidjaja; Grace Setiati Kattu (Intra, 2018)
Indonesia is rich in ethnic groups, languages, religion, etc. Religion is one of the numerous diversities tolerated by the Indonesian. There are 5 religions admitted by the government of Indonesia, namely Catholic, Christian, Islam, Hindu, and Buddha. Christian is one of the most developed beliefs of its time, requiring a space to facilitate worship activity of the Christians. This design aims to present the unique characteristics of GBI ROCK in accordance with its vision and mission, as well as to design a minimalist church with still presenting a sacred impression in worship in order to be closer to God. GBI ROCK City Square is purposedly designed to give the impression of sanctity and the feeling of being closer to God during mass or worship while maintaining the minimalist concept. The main design in the vestry includes Prefunction section as a welcoming area for the congregation and multipurpose section as a facility designated to support the Sunday school.